PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI YAYASAN KESATUAN PENDIDIKAN ISLAM (YKPI) AL-ITTIHAD - Indra Ulfairah Ilma; Machasin Machasin; Pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research was conducted at the Al-Ittihad Islamic Education Unit FoundationPekanbaru. The purpose of this study was to analyze the effect of motivational and workenvironment variables on teacher performance through job satisfaction as an intervingvariable at the Al-Ittihad Islamic Education Unit Foundation. This research is aquantitative research that uses path analysis. This study used a questionnaire datacollection method which was distributed to 100 teachers at the Al-Ittihad IslamicEducation Unit Foundation. The results of this study state that: 1) Work motivation has apositive and significant effect on job satisfaction. 2) Work environment has a positive andsignificant effect on job satisfaction. 3) Work motivation has a positive and significanteffect on teacher performance. 4) The work environment has a positive and significanteffect on teacher performance. 5) Job satisfaction has a positive and significant effect onteacher performance. 6) Work motivation has a positive and significant effect on teacherperformance with job satisfaction as an intervening variable. 7) The work environmenthas a positive and significant effect on teacher performance with job satisfaction as anintervening variable. Keywords: Motivation, Work Environment, Teacher Performance, and Job Satisfaction